Studing the luminescence and excitation of Calcium Fluoride and matching it with computer. - اسماعيل نواف; برهان دالاتي; محمود أحمد (Latakia University Journal -Basic Sciences Series, 2023)
Calcium fluoride was prepared using the chemical precipitation method, The absorption spectrum was taken with a methanol dispersion The oscillator strength of the vibrator was calculated for the possible transitions by matching the experimental absorption spectrum with the theoretical spectrum, assuming that the spectral line shape is Gaussian and the number of spectral lines of the absorption spectrum is seven lines, a decoupling of the experimental absorption curve was made, and then the wavelengths corresponding to the most probable transitions were found. The emission spectrum of the prepared sample was taken at an excitation length of 300 nm and an emission peak was observed at the wavelength of 400 nm.